Bone formation in peri-implant defects grafted with microparticles: a pilot animal experimental study - Moest, Tobias; Koehler, Franz; Prechtl, Christopher; Schmitt, Christian; Watzek, Georg; Schlegel, Andreas (Journal of Clinical Periodontology, 2014)
This study aimed to evaluate the healing of peri-implant defects grafted with microparticles (MPs).Six domestic pigs received nine standardized defects at the calvaria, and an implant was inserted in the middle of each defect. The space between the implant and lateral bone portion was filled with MP pellets (n = 18) or MP supernatant (n = 18) or left unfilled (n = 18). After 14 and 28 days, three animals were sacrificed and specimens removed for further processing. Samples were microradiographically and histologically analysed. In addition, we immunohistochemically stained for anti-vWF as a marker of angiogenesis.In the case of bone regeneration and vessel formation, the null hypothesis can be partially rejected. After 14 and 28 days, no significant difference was observed within groups regarding de novo bone formation, bone density and osseointegration. However, superior vessel formation was found at both time points.Microparticles represent a promising treatment option to accelerate peri-implant vessel formation. Further studies are needed to investigate the regenerative properties of MPs more precisely.
EVALuna2:24388